2021
DOI: 10.3389/feart.2021.662172
|View full text |Cite
|
Sign up to set email alerts
|

Two Sides of the Same Coin: A Combination of Archaeometallurgy and Environmental Archaeology to Re-Examine the Hypothesis of Yunnan as the Source of Highly Radiogenic Lead in Early Dynastic China

Abstract: Bronze Age Shang China is characterized by its large-scale production system and distinctive ritual world. Both are vividly materialized by a large number of bronze ritual vessels with added lead. Whilst a remarkable amount of research effort has been channeled into the trace elemental and lead isotopic analysis of these ritual vessels, and successfully revealed some important fingerprints such as highly radiogenic lead (HRL), there is as yet no consensus on the metal source(s) which supplied the entire bronze… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 65 publications
0
4
0
Order By: Relevance
“…However, this could sabotage the provenance studies via isotope and constitutional characteristics of the artefact to locate the specific resources. The mining and smelting sites and processing relics could not help us reconstruct the details of this 'chaine operatoire' [27] of the bronze artefact. We could still make an approximate approach to this indigenous bronze production tradition.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, this could sabotage the provenance studies via isotope and constitutional characteristics of the artefact to locate the specific resources. The mining and smelting sites and processing relics could not help us reconstruct the details of this 'chaine operatoire' [27] of the bronze artefact. We could still make an approximate approach to this indigenous bronze production tradition.…”
Section: Discussionmentioning
confidence: 99%
“…The isotope investigation was the most popular for the provenance research [27], but in this study, the embraced prill in the processing slag has reflected the remelting and remixing/recycling of different copper raw materials. This scenario was not commonly supported by archaeological discoveries in the bronze age but could not be continually neglected in the iron age [28].…”
Section: Discussionmentioning
confidence: 99%
“…Yunnan was also once believed to be a source of the highly radiogenic lead in the metal produced along the Yellow and Yangtze Rivers (Jin et al, 2017). Although the source of radiogenic lead needs more in-depth research, its distribution reveals another potential route for north-south communication from the Central Plains (the Shang dynasty) and the Wei River Valley (the Zhou dynasty) to Hanzhong, Sichuan (the Sanxingdui culture), and Yunnan (Liu et al, 2021). Meanwhile, lead isotopic analysis, together with the widespread use of bronze drums with vivid and unique decorations in Yunnan, Guangxi, Guizhou, and Southeast Asia, points to close contact—in terms of material culture and raw metal resources – for these regions (Pryce and Bellina, 2018; Pryce et al, 2022) despite not yet having identified the exact routes.…”
Section: Discussionmentioning
confidence: 99%
“…According to his view, copper and lead were involved only because the minerals extracted in Yunnan were polymetallic. Up to now, there is still a lack of any solid archaeological evidence from Yunnan to prove this long-distance transport hypothesis (Liu et al , 2021).…”
Section: Provenance Versus Mixing and Recycling: Highly Radiogenic Le...mentioning
confidence: 99%